Campylobacter novaezeelandiae sp. nov., isolated from birds and water in New Zealand. Issue 6 (5th June 2020) - Bloomfield, Samuel; Wilkinson, David; Rogers, Lynn; Biggs, Patrick; French, Nigel; Mohan, Vathsala; Savoian, Matthew; Venter, Pierre; Midwinter, Anne
Abstract : Six isolates of Campylobacter with similar non-standard colonial morphologies were identified during studies isolating Campylobacter from bird faeces and rivers in New Zealand. Genomic (16S rRNA gene sequencing and whole genome analysis) and phenotypic (MALDI-TOF analysis and conventional biochemical tests) showed that the isolates form a monophyletic clade with genetic relationships to Campylobacter coli / Campylobacter jejuni and Campylobacter peloridis / Campylobacter amoricus . They may be distinguished from other Campylobacter by their MALDI-TOF spectral pattern, their florid α-haemolysis, their ability to grow anaerobically at 37 °C, and on 2 % NaCl nutrient agar, and their lack of hippuricase. This study shows that these isolates represent a novel species within the genus Campylobacter for which the name Campylobacter novaezeelandiae sp. nov. is proposed. The presence of C. novaezeelandiae in water may be a confounder for freshwater microbial risk assessment as they may not be pathogenic for humans. The type strain is B423b T (=NZRM 4741 T =ATCC TSD-167 T ).